CO2, CH4 and N2O emissions after fertilizer application in banana plantations located in the Brazilian Atlantic Forest - Silva, Reginaldo Barboza da [UNESP]; Antunes, Taline [UNESP]; Rosa, Jéssica Silva [UNESP]; Packer, Ana Paula; Bento, Camila Bolfarini; Carmo, Janaina Braga do; Silva, Francisca Alcivânia de Melo [UNESP] (Wiley, 2022)
Bananas are important tropical fruits conventionally cultivated under intensive nitrogen fertilization. A current challenge is to understand the environmental impacts of this crop across the different cultivation stages considering greenhouse gas emissions. Therefore, the present study evaluated whether inorganic fertilization with ammonium sulphate and urea during different planting stages can change soil CO2, CH4 and N2O emissions. The experiment was conducted in 2018 in an Atlantic Forest region of São Paulo State, Brazil. We used the chamber-based methodology for gas sampling in young and established banana plantations and in a forest remnant fragment. Seasonal differences in temperature and rainfall during the sampling period resulted in a larger WFPS during the wet season. The CO2 emissions followed the rainfall variations. CH4 fluxes were mainly resulted of methanotrophy reactions. The maximum and minimum N2O fluxes were 7.38 and −0.93 mg m2 day−1, peaking after nitrogen fertilization. We found that the accumulated N2O fluxes from soil were greater for the two banana plantations than those observed in the forest remnant in dry and wet seasons. The highest N2O peaks were observed in the young banana plantation. CH4 uptake was 92 and 61% less in young and established banana plantations than in the forest remnant, while N2O emissions were 95 and 74% greater in young and established banana plantations than in the forest remnant. Considering the negative effect of N2O emissions, reduced rates of nitrogen application and the adoption of conservation practices should be considered in young banana plantations.
Keywords: carbon dioxide; climate change; forest remnant; GHG; methane; nitrous oxide